156 Independent Associations With 30- and 90-Day Unplanned Readmissions After Elective Lumbar Spine Surgery: A National Trend Analysis of 144 123 Patients. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Elsamadicy, Aladine A; Ren, Xinru; Kemeny, Hanna; Charalambous, Lefko; Rahimpour, Shervin; Williamson, Theresa; Goodwin, C. Rory; Abd-El-Barr, Muhammad M; Gottfried, Oren N; Xie, Jichun; Lad, Nandan
Abstract: INTRODUCTION: Recently, Centers for Medicare & Medicaid Services implemented initiatives to penalize hospitals financially for unplanned 30-d hospital readmission rates. However, there is a paucity of data identifying modifiable patient risk factors that are independently associated with 30- and 90-d readmissions. The aim of this study was to determine patient risk factors associated with 30- and 90-d unplanned readmission following elective lumbar-spine surgery. METHODS: The National Readmission Database was queried to identify all patients who underwent elective lumbar-spine surgery for the 2013 and 2014 calendar years. Patients were grouped by no readmission(non-R), within 30 d (30-R) and 31 to 90 d (90-R) of hospital discharge. Patient demographics, comorbidities, hospital characteristics, and 30- and 90-d complication rates were collected. The primary outcome of interest was the rate of unplanned 30- and 90-d readmission rate and associated patient risk factors. A multivariate analysis was used to determine patient factors that were independently associated with unplanned 30- and 90-d readmission after elective lumbar-spine surgery. RESULTS: We identified 144 123 patients who underwent elective lumbar-spine surgery with 10 592(7.3%) patients experiencing an unplanned hospital readmission (30-R: n = 7228, 90-R: n = 3364, non-R: 133 531). Baseline patient demographics, comorbidities, and hospital characteristics were similar between both cohorts. Spinal fusion was the most common spinal procedure with the highest readmission rates (30-R: 42.4%, 90-R: 38.8%). The most common inpatient complication observed was dural tear (30-R: 7.7%, 90-R: 4.6%, non-R: 4.3%). The most prevalent 30- and 90-d complication was infection (30-R: 18.5%, 90-R: 7.4%). In a multivariate regression analysis, age, insurance status (Medicare, Medicaid, and Self-Pay), chronic obstructive pulmonary disorder, depression, hypertension, diabetes, deficiency anemia, and obesity were independently associated with 30-d unplanned hospital readmission, while age and obesity were not independently associated with 90-d unplanned hospital readmission. CONCLUSION: Our study identified several patient demographics and modifiable comorbidities that were similar and independently associated with both 30- and 90-d unplanned readmissions.